2013
DOI: 10.1080/07294360.2013.832158
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry professors’ descriptions of the impact of research engagement on teaching

Abstract: Professors endorse a symbiotic relationship between research and teaching, but empirical evidence supporting this relationship is inconsistent. Many studies operationalized research and teaching too narrowly to detect the believed relationship. Semi-structured, in-depth interviews were conducted with 27 chemistry professors from a large research-intensive university. Six themes characterized descriptions of how professors' research engagement affects their teaching: it (1) enhances student interest, (2) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The integration of research into university teaching has strong potential for fostering a deeper understanding of disciplinary knowledge (Hua and Shore 2014;Vereijken et al 2018). There are multiple ways in which research is articulated in teaching in order to foster student understanding of disciplinary knowledge.…”
Section: Teaching Theory and Practicementioning
confidence: 99%
“…The integration of research into university teaching has strong potential for fostering a deeper understanding of disciplinary knowledge (Hua and Shore 2014;Vereijken et al 2018). There are multiple ways in which research is articulated in teaching in order to foster student understanding of disciplinary knowledge.…”
Section: Teaching Theory and Practicementioning
confidence: 99%
“…Also, a study from Hua and Shore (2013), using the same sample as the one in our study, revealed six ways in which chemistry professors' engagement in research activities strengthened their teaching practice, including student interest, subject-matter currency, research examples, ways of thinking (e.g., how research helps them appreciate differences between "what is" and "what we know" and demonstrate "how [we] know this is true"), contextualization, and explanation (e.g., how concepts, principles, and facts are organized in chemistry). Professors' belief that active engagement through research helped them provide better explanations of the material to improve student understanding represented a promising base from which to conduct the current study and re-evaluate professors' perceptions of undergraduate learning.…”
Section: Methodsmentioning
confidence: 99%
“…In these contexts, it is frequently introduced as an example of cutting-edge research. FLP chemistry certainly qualifies as such and incorporating research topics into undergraduate instruction can be a valuable strategy for not only engaging students, but engaging faculty as well [26].…”
Section: Introductionmentioning
confidence: 99%